Development of Local Wisdom-based Islamic Education Learning Material for Secondary School Students: A Design-based Research - Desi Erawati; Rahmayanti Rahmayanti (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
Teaching material was important component in teaching and learning process. This study aimed to develop teaching material for Islamic religion education which was based on local wisdom for secondary school students. This study used a design-based research method where teaching materials were developed based on local characteristics of students in the area of Palangka Raya, Central Kalimantan. Data were obtained through interviews and direct observation. Interviews were conducted with education practitioners and teachers to obtain preliminary data related to local issues relevant to be integrated in learning material. The results showed that learning material contained local wisdom in the form of content related to the environment and care for the environment in accordance with the teachings of Islam. Therefore, the development of environmental-based Islamic Education learning provides real understanding to students because it was adapted to the real conditions of the surrounding nature such as forest, rivers, and extensive plantation land. The material taught was interesting and innovative, also implementative in its social practice. Keywords: Islamic Teaching and Learning, Local Wisdom Islamic Education, Learning Material